Survival among children and adults treated with granulocyte transfusions: Twenty years' experience at a Brazilian blood center. (April 2022) - de Almeida-Neto, Cesar; Corso, Lucas Machado; Bassolli, Lucas; Witkin, Steven S.; Hamasaki, Debora Toshie; Albiero, André Luís; Manangão, Caroline Limoeiro; Mendrone-Junior, Alfredo; Rocha, Vanderson
Abstract: Background: It remains controversial whether granulocyte transfusions as a supportive treatment improve survival in patients with febrile neutropenia or granulocyte dysfunctions. We describe survival rates subsequent to granulocyte transfusions in pediatric and adults patients treated at a major blood center in Brazil. Material and methods: We retrospectively reviewed the clinical charts of pediatric and adult patients treated with granulocyte transfusions at our institution from January 2000 to October 2019. We assessed demographic characteristics, clinical features, indications for transfusion, units transfused, dose of granulocytes administered and survival rates 30 and 100 days after the initial transfusion. Results: We identified 64 pediatric and 67 adult patients treated with 262 granulocyte transfusions. An optimal dose (> 0.6 × 10 9 granulocytes per kilogram per transfused unit) was available for transfusion in 80.4 % of pediatric patients but in only 19.6 % of adults (p = 0.017). Thirty days after their first granulocyte transfusion, 38 (59.4 %) pediatric and 61 (91 %) adult patients had died. Patients receiving the optimal dose of granulocytes had better survival outcomes, but even among this sub-group, adults were more likely to die than were children either at 30 days (OR = 8.67, 95 %CI 2.69–34.9) or 100 days (OR = 6.27, 95 %CI 1.86–25.9) after their initial granulocyte transfusion. Conclusion: Survival rates following granulocyte transfusion varied by the dose transfused and were higher in children than in adults.